2010
DOI: 10.1007/s00442-009-1551-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific alkaloid variation in ladybird eggs and its effects on con- and hetero-specific intraguild predators

Abstract: Egg predation and cannibalism are common phenomena in predatory ladybirds despite the presence of defensive alkaloids. Consumption of heterospecific eggs negatively affects survivorship and development; however, intraspecific variation in quantities of alkaloids and post-ingestion responses to con- and hetero-specific alkaloids, are not well understood. We examined variation in the quantity of alkaloids in eggs of Harmonia axyridis (Pallas), Coccinella septempunctata L., and Hippodamia convergens (Guérin) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 46 publications
6
61
2
2
Order By: Relevance
“…In addition, the ladybirds studied may utilize the nutrients in aphids with greater efficiency than those in con-or heterospecific eggs, which could also result in larvae taking less time to develop and bigger adults. The results are in agreement with many previous studies (Sato & Dixon, 2004;Cottrell, 2007;Sloggett et al, 2009;Kajita et al, 2010;Hemptinne et al, 2011). Further, because of its higher consumption rates, conversion efficiencies and growth rates the immature stages of C. septempunctata developed faster and the adults were bigger when fed on aphid or eggs than were those of C. transversalis.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the ladybirds studied may utilize the nutrients in aphids with greater efficiency than those in con-or heterospecific eggs, which could also result in larvae taking less time to develop and bigger adults. The results are in agreement with many previous studies (Sato & Dixon, 2004;Cottrell, 2007;Sloggett et al, 2009;Kajita et al, 2010;Hemptinne et al, 2011). Further, because of its higher consumption rates, conversion efficiencies and growth rates the immature stages of C. septempunctata developed faster and the adults were bigger when fed on aphid or eggs than were those of C. transversalis.…”
Section: Discussionsupporting
confidence: 94%
“…As mentioned above, intraguild predation among predatory ladybirds may explain why H. axyridis can successfully outcompete native ladybirds (Gardiner et al, 2011). For example, A. bipunctata beetles die when feeding on H. axyridis eggs or larvae, but H. axyridis beetles suffer no ill effects when the relationship is reversed (Kajita et al, 2010). Accordingly, we found that microsporidia associated with H. axyridis kill A. bipunctata adults feeding on H. axyridis eggs (Vogel et al, 2017a).…”
Section: Immunity and Invasive Performancesupporting
confidence: 50%
“…Many laboratory assays indicate its higher toxicity and/or unpalatability compared to other members of aphidophagous guilds (ladybirds, lacewings) (Phoofolo and Obrycki 1998;Cottrell 2004;Sato and Dixon 2004;Kajita et al 2010;Nedvȇd et al 2010). Further protection of the larvae is provided by spiny projections on their cuticle.…”
Section: Homalotylus Spp (Hymenoptera: Encyrtidae)mentioning
confidence: 99%